Improved flowsheet of wastewater treatment from nitrogen a containing compounds - Semenova, Olena; Reshetnyak, Lyudmila; Bublienko, Natalia; Salavor, Oksana; Smirnova, Elizabeth (My University, 2015)
Waste water containing nitrogen compounds stimulate the growth of plankton, algae and violate the oxygen regime, affecting the livelihoods of aquatic organisms. Wastewater treatment of nitrogen carried activated sludge in suspended state or immobilized using active biomass.
Keywords: кафедра екології та екоменеджменту; кафедра іноземних мов професійного спрямування; wastewater; vitrification; denitrification; biologicaltreatment; aerotank; стічна вода; нітрифікація; денітрифікація; біологічне очищення; аеротенк